2018
DOI: 10.1371/journal.pone.0191390
|View full text |Cite
|
Sign up to set email alerts
|

Egg turning behavior and incubation temperature in Forster’s terns in relation to mercury contamination

Abstract: Egg turning behavior is an important determinant of egg hatchability, but it remains relatively understudied. Here, we examined egg turning rates and egg temperatures in Forster’s terns (Sterna forsteri). We used artificial eggs containing a data logger with a 3-D accelerometer, a magnetometer, and a temperature thermistor to monitor parental incubation behavior of 131 tern nests. Overall, adults turned their eggs an average (±SD) of 3.8 ± 0.8 turns h-1, which is nearly two times higher than that of other seab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 65 publications
2
12
0
Order By: Relevance
“…However, our results do not report any relationships between PFASs/Hg and T inc . This is supported by a recent investigation by Taylor et al (), who found no relationship between egg Hg contamination and T inc of Forster terns. Thus, our research contributes to filling the gap in knowledge, but additional studies are needed to confirm the generality of our findings in other bird species and, importantly, targeting the specific chemicals involved in avian T inc variations.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…However, our results do not report any relationships between PFASs/Hg and T inc . This is supported by a recent investigation by Taylor et al (), who found no relationship between egg Hg contamination and T inc of Forster terns. Thus, our research contributes to filling the gap in knowledge, but additional studies are needed to confirm the generality of our findings in other bird species and, importantly, targeting the specific chemicals involved in avian T inc variations.…”
Section: Discussionsupporting
confidence: 75%
“…Using artificial egg loggers, we investigated whether the most contaminated kittiwakes were less committed in incubating their clutch and less able to provide appropriate egg warming. Embedded in artificial eggs, these loggers can provide almost continuous (every second) and precise recording of incubation behaviors (Shaffer et al ; Kelsey et al ; Clatterbuck et al ; Taylor et al ). Specifically, we examined the relationships between blood levels of 3 groups of contaminants (organochlorines, PFASs, and Hg) and T inc in a kittiwake population from Svalbard in the Norwegian Arctic.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the temperatures reported here are well below the known incubation ranges for terns (e.g. Taylor et al 2018), providing further evidence that iButtons would not be sufficient for measuring exact egg temperatures but provide a sufficient proxy for the purposes of our work.…”
Section: Natural Bout Characteristicsmentioning
confidence: 62%
“…The nest characteristics of COTE also proved to be a challenge, as the simple scrape nest structure allowed iButtons in unattended nests to be easily covered with windblown sand and invalidate subsequent data. Researchers should carefully consider their objectives and the use of other logger techniques (i.e., Arnold et al 2006;Taylor et al 2018) if windblown substrate is likely to present a challenge.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation